PE teachers' perceived expertise and professional development requirements in the delivery of muscular fitness activity: PE Teacher EmPOWERment Survey. (May 2023) - Cox, Ashley; Noonan, Robert J.; Fairclough, Stuart J.
Muscular fitness (MF) is an important modifiable factor to improve overall health. Schools offer a unique opportunity to deliver MF activity during physical education (PE) and develop competence to engage in various activities across the life course. However, the implementation of school-based MF activity may be impaired by some teachers reporting a lack of expertise and low confidence in the delivery of MF activity. Understanding teachers' thoughts and perceptions regarding the delivery of MF in schools may help guide future research and policy to support MF delivery in UK schools. Following ethical approval, a survey of secondary school PE teachers across the UK was distributed via Twitter. Survey responses were analysed and reported descriptively and thematically. Completed surveys were returned by 194 teachers (61.9% male) from England, Scotland, Wales, and Northern Ireland. Relative to less experienced teachers, those with at least five years' service were 2.2 times more likely to have completed continued professional development (CPD) in MF activity (OR = 2.16; ß = 0.77; 95% CI: 1.25-3.74; p < 0.01), and 1.8 times more likely to use assessments of MF to inform PE programme decision-making (OR = 1.83; ß = 0.60; 95% CI: 1.18-2.82; p < 0.01). Despite the promising contribution school-based PE may have to developing MF, we report a poor understanding of MF activity amongst UK-based PE teachers. CPD is warranted to deliver successful MF interventions in a school setting.